Concordance and Validity of Urinalysis Using Sysmex UX-2000, Cobas U411 and Manual Microscopic Examination - Anak Agung Wiradewi Lestari (Journal of Global Pharma Technology, 2019)
Objective: Urinalysis is important in screening, diagnosing, and monitoring the progress of certain diseases. However, the procedure takes time to finish, special skill, and lack of standardization in certain labs. This study evaluates the concordance between manual microscopic examination results to Sysmex UX-2000, and urinalysis chemical results between Sysmex UX-2000 and Cobas U411 (Roche Diagnostic), and the validity of urine sediment results between Sysmex UX-2000 and manual microscopic examination.  Methods: Eighty urine samples were analyzed using Sysmex UX-2000, Cobas u411, and manual microscopic examination. Concordance level was measured using kappa coefficient. Then we calculated the validity of Sysmex UX-2000 in sediment tests to manual microscopic examination. Results: Chemical urinalysis of Sysmex UX-2000 possesses good and very good concordance level to Cobas u411 (*weighted κ 0.65-0.91). Urine sediment tests of Sysmes UX-2000 possesses good concordance to manual microscopic examination (**weighted κ 0.76-0.77), with 86-100% sensitivity and 73-78% specificity. Conclusion: Sysmex UX-2000 has good concordance level to Cobas u411 for chemical tests urinalysis, and also good concordance and validity between Sysmex UX-2000 to microscopic examination for erythrocyte and leucocyte sediment tests.Keywords: Analytical System, Renal Diseases, Quality Assurance and Control.